Using Miniaturized Strain Sensors to Provide a Sense of Touch in a Humanoid Robotic Arm - Belford, Andrew; Moshizi, Sajad A.; Razmjou, Amir; Asadnia, Mohsen (Frontiers in Mechanical Engineering, 2020)
Recent advancements in sensing technology have led to developments of lighter and smaller control systems for prosthetic and biomedical applications. In this paper, we develop a bio-inspired sensory system for a master-slave force-sensing robotic hand which allow accurate control and provide a natural sense of touch to humanoid robotic hand based on force information derived from a smart glove equipped. The slave robotic hand is fabricated using three-dimensional (3D) printing technology, with servo motors to actuate the hand components. A glove with miniaturised flexible sensors attached serves as the master robotic hand, providing movement and force signals for the slave to emulate. The signals from the force sensors are used to moderate the movement of the slave hand’s fingers, so allowing delicate objects to be handled without the risk of breakage. We show that this is a practical and versatile method to improve robotic handling, and that with careful selection and tuning, it is possible to track the master hand’s applied force to within 0.1 Newtons. The success of this approach will pave the way for the development of novel control systems using low-cost bio-inspired strain and force sensors for prosthetics applications.